Fláajökull (north lobe), Iceland : active temperate piedmont lobe glacial landsystem. - Evans, D.J.A.; Ewertowski, M.; Orton, C. (Journal of Maps, 2016)
A 1:6250 map of the foreland of Fláajökull's north lobe as it appeared in 1989, together with a 1:350 scale map of a sample area of recently exposed glacial landforms from 2014, enables an assessment of the spatial and temporal evolution of glacial landform assemblages at the margin of an active temperate piedmont lobe terminating at ice-marginal thickening till wedges. The pattern of landform development captured in these maps indicates that the glacier margin developed strong longitudinal crevassing and well-developed ice-marginal pecten (three-dimensional crenulations) during its historical recession. This is recorded by early recessional phase linear push moraines on well-drained distal slopes of the foreland and the later development of interrelated sawtooth moraines, crevasse squeeze ridges and till eskers, indicative of extending ice flow and poorly drained submarginal conditions. This landform record is a palaeoglaciological signature of a changing process–form regime inherent within the active temperate piedmont lobe landsystem model.